Assemblages of violence in education : everyday trajectories of oppression - Wozolek, Boni, 1984- (New York, NY : Routledge, 2021)
"Artfully weaving participant narratives in two contexts that exist a literal world apart-queer middle school youth of color in an urban context and Indian women who have survived domestic violence-this book conceptualizes how social justice functions in opposition to normalized aggressions. Written for students and professors in curriculum studies, sociology of education, critical race studies, and gender studies, this volume draws upon international contexts to highlight daily, interconnected oppressions within educational settings"--
OCLC-licensed vendor bibliographic record.
Keywords: Social justice and education -- Cross-cultural studies; Victims of violent crimes -- Psychological aspects; Quantum entanglement; EDUCATION / General